A CROSS-SECTIONAL STUDY ON THE IMPLEMENTATION OF RESULTS-BASED FINANCING TO IMPROVE MATERNAL, NEWBORN, AND CHILD HEALTH (MNCH) SERVICES IN NATIONAL REFERRAL HOSPITALS IN UGANDA - Isiko, Geofrey (Student’s Journal of Health Research Africa, 2025)
Background Results-based financing (RBF) is one of the health financing schemes implemented in Uganda’s health care system to improve access and utilization of quality health services. This study evaluated the implementation of RBF for MNCH service delivery in national referral hospitals in Uganda. Methods The study employed a qualitative research approach and a cross-sectional research design with Kawempe National Referral Hospital as the study area. 12 participants were selected purposively from Kawempe National Referral Hospital, Ministry of Health Uganda, ENABEL-Belgian Development Agency, and Uganda Reproductive, Maternal and Child Health Services Improvement Project (URMCHIP). Data was collected through interviews and document reviews. Results The study reported that RBF increased resources used to purchase critical drugs and equipment, staff recruitment, and infrastructure development, as well as better indicators in MNCH service delivery. However, challenges such as inadequate supervision, fund misallocation, poor model design, and unclear fund management persisted. The study recommended enforcing supervision, revising resource allocation, and disbursing funds on time. Conclusion The implementation of RBF for MNCH service delivery in national referral hospitals in Uganda has improved MNCH outcomes as well as the quality of services provided. However, the existing challenges need to be addressed to ensure that the intended goals and objectives are achieved.